Immune Modulation for Enzyme Replacement Therapy in A Female Patient With Hunter Syndrome - Julien, Daniel C.; Woolgar, Kara; Pollard, Laura; Miller, Holly; Desai, Ankit; Lindstrom, Kristin; Kishnani, Priya S. (Frontiers in Immunology, 2020)
A 3.5 year old Hispanic female presented with signs and symptoms concerning for MPS II (Hunter Syndrome). The diagnosis of MPS II was confirmed by enzyme and molecular testing. Genetic evaluation revealed undetectable plasma iduronate-2-sulfatase enzyme activity and an inversion between intron 7 of the IDS gene and a region near exon 3 of IDS-2. This inversion is the molecular cause for approximately 8% of cases of MPS II and often results in a severe phenotype. X-inactivation studies revealed an inactivation ratio of 100:0. Given the patient’s undetectable enzyme level, in combination with a severe IDS gene mutation, classic features at time of presentation, and the significantly skewed X inactivation, there was concern that she was at high risk of developing high and sustained antibody titers to idursulfase which would limit her benefit from enzyme replacement therapy (ERT). Anti-drug neutralizing antibodies to idursulfase have been associated with reduced systemic exposure to idursulfase and poorer clinical outcomes. Therefore, the decision was made to concurrently treat the patient with immune tolerance induction therapy during the first month of treatment with idursulfase in order to decrease the risk of developing high sustained antibody titers. The immune tolerance induction protocol consisted of rituximab weekly for four weeks, methotrexate three times a week for three weeks and monthly IVIG through B-cell and immunoglobulin recovery. Immune tolerance induction was initiated concurrently with the start of ERT. The patient had no significant adverse effects related to undergoing immune tolerance induction therapy and two and half years later is doing well with significantly reduced urine glycosaminoglycans and very low anti-drug antibody titers. This immune tolerance induction protocol could be considered for other patients with MPS II as well as patients with other lysosomal storage disorders who are starting on enzyme replacement therapy and are at high risk of developing neutralizing anti-drug antibodies.